A new species of Atanatolica Mosely 1936 (Trichoptera: Leptoceridae) from Serra Bonita, Bahia, Brazil - Costa, Anne M.; Calor, Adolfo R. (Zootaxa, 2014)
The Neotropical genus Atanatolica includes 17 species distributed from Costa Rica to Brazil, but only two, A. brasiliana and A. flinti, have been recorded from Brazil, both occurring in Rio de Janeiro and São Paulo States. A new species, Atanatolica bonita n. sp., is described and illustrated based on males and females from the Atlantic Forest in Bahia State in northeastern Brazil. The new species can be diagnosed by the following characters: Apicomesal and apicolateral processes of segment X of same length, long and digitate; and second article of each inferior appendage well developed, long, and thumb-shaped. Notes on demographic changes and correlations with seasonal variation and precipitation are also given.